Chromenopyridines: Promising Scaffolds for Medicinal and Biological Chemistry - J. Nunez-Vergara, L.; A. Squella, J.; A. Navarrete-Encina, P.; Vicente-Garcia, E.; Preciado, S.; Lavilla, R. (Current Medicinal Chemistry, 2011)
Chromenopyridines constitute a structurally diverse class of compounds with a wide range of bioactivities and increasing presence in drugs. Here we analyze the scope of the synthetic methodology to access this nucleus with emphasis on multicomponent reactions and robust methodologies. Reactivity issues, medicinal applications and other properties are also reviewed.
Keywords: coumarin